2005
DOI: 10.1097/00004356-200503000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of traumatic spinal cord injuries in south-eastern Anatolia, Turkey: a comparative approach to 10 years?? experience

Abstract: The purpose of this study was to determine the demographic and epidemiological characteristics of traumatic spinal cord-injured patients. The hospital records of 539 patients (416 men, 123 women) with spinal cord injuries (SCIs) admitted to four hospitals that were major referral centers for trauma in the south-eastern region of Turkey from 1990 to 1999 were reviewed retrospectively. The patients with SCI were investigated for two periods; the first period covered patients admitted between 1990 and 1994 during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
2
24
2
2
Order By: Relevance
“…Again, in a series of 95 cases, Dickson et al reported that there were 71 men (74.7%) and 24 women (25.3%), while Roy Camille et al reported that there were 75 men (65.2%) and 40 women (34.8%) in a series including 115 patients [5,8]. Consistent with literature, in our study 29.6% were women while 70.4% were men.. Spinal traumas are more frequent in the second and fourth decades [9]. Median age at the time of trauma can vary between developed and developing countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Again, in a series of 95 cases, Dickson et al reported that there were 71 men (74.7%) and 24 women (25.3%), while Roy Camille et al reported that there were 75 men (65.2%) and 40 women (34.8%) in a series including 115 patients [5,8]. Consistent with literature, in our study 29.6% were women while 70.4% were men.. Spinal traumas are more frequent in the second and fourth decades [9]. Median age at the time of trauma can vary between developed and developing countries.…”
Section: Discussionsupporting
confidence: 88%
“…Spinal traumas are observed at 35-54 years of age in developed countries. However, it was found that risk for spinal injury is significantly increased at 20-40 years of age in developing countries [9,11]. In our study, the mean age was 41.3 years.…”
Section: Discussionmentioning
confidence: 42%
“…An earlier study performed in a region of Turkey between 1990 and 1999 found that the proportion of GSWSCI was 21.3%. 13 A study conducted at our Center between 2000 and 2007 revealed that the proportion of GSWSCI was 12.2%, as the third most common cause of SCI. 11 In the present study, patients with GSWSCI accounted for 9.8% (102/1043) of all admissions during the study period.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12][13] Although the proportion of these etiologies is almost similar in different countries, GSWSCI, which has an important place in the etiology of SCI, has a rather wide range of proportion among all causes of SCI. In some countries, GSWSCI exceeds motor vehicle accident or falls, whereas it is considerably lower in others.…”
Section: Discussionmentioning
confidence: 99%
“…Тако Karacan и Burke у својим епидемиоилошким студијама наводе да је најчешћи скелетни ниво повређивања у вратном делу Ц5 и Ц6, у торакалном Т12, и у лумбалном Л1 и Л2 нивоу. Pickett и аутори наводе сличне резултате [51]. Овакви резултати наше и осталих студија потврђују тезу о анатомским и биомеханичким особеностима вратне и лумбалне регије кичменог стуба.…”
Section: дискусијаunclassified